Expansão urbana de Mossoró : período de 1980 a 2004 - Rocha, Aristotelina Pereira Barreto (2005)
The purpose of this Academic Work is to identify the process of urban expansion of Mossoro city, connect them with the economy that moves the society of Mossoro. This analysis is about the period from 1980 to 2004 and the economy activities selected are compose the structure of the Mossoro' s life, fixing shapes, functions and contents of the city territory, especially in its urban space to understand the present process of urban expansion and its relations with the dynamic of the city we recall history of this territory, wich as a urban word, connect the changes with the primary economy actives - commerce and sea salt extraction. ln this relation between the present process of urban expansion and the dynamic of the city economy, the economy activities studies where the sea salt extraction, and irrigated fruit crops organizes the space so they can be viable in all stages - production, trade and circulation - to be viable they change, amplify and build a urban space together with public policy, that also increases with the arrival of new inhabitant, service structure, mount by the public administration as well as by private resources. This work point out the needs of a development a new main plan for Mossoro, that will reorganize it's territory, but also grant the needs of its society, wich desires a more given city, where citizenship will be exercise with dignity